Assimetria flutuante em duas espécies de marsupiais (gracilinanus agilis e monodelphis domestica) em um fragmento do semiárido brasileiro - Barros, Luiz Fernando Clemente (Universidade Federal Rural do Semi-Árido, 2017)
Fluctuating asymmetry is an example of differences between sides of a symmetry plane, which can be caused by environmental disturbances and/or genetic disorders. One of the most common causes of environmental disturbances is the fragmentation of habitats, which generates stress during the development stage of the organisms and causing changes in morphological traits. This study assessed the differences between sides of three bilateral morphological traits of two species of marsupials, Monodelphis domestica and Gracilinanus agilis, from a forest fragment in the Caatinga biome, Rio Grande do Norte (Brazil). Between August 2014 and June 2016, 111 individuals from the two species (46 Monodelphis domestica and 65 Gracilinanus agilis), comprising different sexes and ages, were sampled. Results indicate that there is sexual dimorphism in both species, with males being bigger than females. Juveniles of G. agilis presented larger ears than adults, which could indicate some degree of wear through time of this trait and hinder fluctuating asymmetry values. Although this study was conducted in a forest fragment, low levels of FA may indicate that this area is recovering from previous impacts and well connected to other fragments. Smaller M. domestica individuals presented greater FA values than larger individuals, which indicates they may be under stress. In addition, M. domestica larger individuals may have come from surrounding areas with less environmental pressure, which would also indicate that the studied fragment is in recovery. Further results show that asymmetry in both species cannot be represented by a single trait. When comparing the composite fluctuating asymmetry indexes between species, G. agilis presented greater FA than M. domestica, which could be related to different habits and body size. Finally, comparison with previous works is hindered by missing information and the use of different indexes and future research should ameliorate this issues
Keywords: Estresse; pequenos mamíferos; indicador ambiental; marsupial; Caatinga; Stress; small mammals; environmental indicator; marsupial; Caatinga; CIENCIAS AGRARIAS::MEDICINA VETERINARIA